Islamisasi Ilmu Pengetahuan - Maschanif, Siti Mahmudah Noorhayati (Al-Riwayah : Jurnal Kependidikan, 2015)
The progress of knowledge achieved by Moslems in the classical era was related to the interactions between Islam and various existed cultures. This interaction produced some new things because of their openness, the selectiveness, and creativity. As a result, they were able to develop their knowledge and Islamize all aspects their live in terms of ontology, epistemology, and axiology, beside they expressed in Arabic language (as an “Islamic language”). Now days, science that have been known by human being, who make them overcame strongly by many problem what it’s faced. So to face this problem, science and knowledge is very significant and event urgent to discuss, especially if we see the secularization and science islamization. Then, this paper is discoursed that; what is secularization and islamization of science (knowledge) and how will the secularization and islamization of science be researched from ontology, epistemology and axiology aspects.